The Digital Scalpel: How AI and VR are Reshaping the Future of Medical Education - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The landscape of medical education is on the cusp of a profound transformation, driven by the convergence of Artificial Intelligence AI and Virtual Reality V...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care